Intrastriatal Administration of Exosome-Associated Pathological Alpha-Synuclein Is Not Sufficient by Itself to Cause Pathology Transmission - Karampetsou, Mantia; Sykioti, Vasia Samantha; Leandrou, Emmanouela; Melachroinou, Katerina; Lambiris, Alexandros; Giannelos, Antonis; Emmanouilidou, Evangelia; Vekrellis, Kostas (Frontiers in Neuroscience, 2020)
Α-synuclein (α-syn) has been genetically and biochemically linked to the pathogenesis of Parkin-son’s Disease (PD). There is accumulating evidence that misfolded α-syn species spread between cells in a prion-like manner and seed the aggregation of endogenous protein in the recipient cells. Exosomes have been proposed to mediate the transfer of misfolded α-syn and thus facilitate disease transmission, although the pathologic mechanism remains elusive. Here we investigated the seeding capacity of exosome-associated α-syn, in vivo. Disease-associated α-syn was present in exosome fractions isolated from transgenic A53T mouse brain. However, following intrastriatal injection of such exosomes in wt mice we were not able to detect any accumulation of endogenous α-syn. In addition, recombinant, fibrillar α-syn, when loaded to isolated brain exosomes induced minor pathologic α-syn brain accumulation at seven months post injection. These data suggest that exo-somes neutralize the effect of toxic αsyn species and raise additional questions on their paracrine modulatory role in disease transmission.